2021
DOI: 10.1038/s42005-021-00716-y
|View full text |Cite
|
Sign up to set email alerts
|

Size and profile of skyrmions in skyrmion crystals

Abstract: Size is a fundamental quantity of magnetic skyrmions. A magnetic skyrmion can be a local circular object and in an isolated form. A skyrmion can also coexist with a group of its siblings in a condensed phase. Each skyrmion in a condensed phase takes a stripe shape at low skyrmion density and a circular shape at high skyrmion density. Skyrmions at high density form a skyrmion crystal (SkX). So far, skyrmion size in an SkX has not been seriously studied. Here, by using a generic chiral magnetic film, it is found… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 46 publications
0
39
0
Order By: Relevance
“…Importantly, D 0sky strictly depends on the parameters of the microscopic Hamiltonian. In this respect, the determination of the skyrmion size for an isolated skyrmion by computing the skyrmion radius (both equilibrium and average) has recently been proved according to different analytical theories based on the minimization of the skyrmion energy with respect to the skyrmion radius [9,48,49]. In particular, it has been shown that both the average skyrmion size and the wall width separating the core from the outer domain of the skyrmion can be accurately computed [48].…”
Section: Negentropy and Landauer's Limit For A Magnetic Skyrmionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, D 0sky strictly depends on the parameters of the microscopic Hamiltonian. In this respect, the determination of the skyrmion size for an isolated skyrmion by computing the skyrmion radius (both equilibrium and average) has recently been proved according to different analytical theories based on the minimization of the skyrmion energy with respect to the skyrmion radius [9,48,49]. In particular, it has been shown that both the average skyrmion size and the wall width separating the core from the outer domain of the skyrmion can be accurately computed [48].…”
Section: Negentropy and Landauer's Limit For A Magnetic Skyrmionmentioning
confidence: 99%
“…In particular, it has been shown that both the average skyrmion size and the wall width separating the core from the outer domain of the skyrmion can be accurately computed [48]. This investigation has been generalized by studying the magnetic skyrmion's size and spin profile in a condensed phase forming a skyrmion crystal at high skyrmion density [49]. In this latter case, it has been demonstrated that the dependence of skyrmion size on magnetic parameters is different compared to isolated skyrmions or to skyrmion stripes forming at low skyrmion density.…”
Section: Negentropy and Landauer's Limit For A Magnetic Skyrmionmentioning
confidence: 99%
“…With that being said, the exact demagnetization field is automatically included in all of our MUMAX3 simulations [39]. It is known that isolated circular skyrmions are metastable state when κ = π 2 D 2 /(16AK ) < 1 [38,40].…”
Section: Model and Methodsmentioning
confidence: 99%
“…In the polar coordinates (r,φ), the normalized magnetization is m = (sin cos , sin sin , cos ), where the polar angle of the magnetization of a skyrmion centered at r c can be well described by [38,40] (…”
Section: Model and Methodsmentioning
confidence: 99%
“…Magnetic skyrmions [1][2][3][4][5] are topological magnetic solitons characterized by a topological number, which have drawn a lot of attention in spintronic applications due to their small size, topological stability, and low density of driving current. Generally, the presence of bulk, interfacial, or anisotropic Dzyaloshinskii-Moriya interactions (DMI) [6][7][8][9][10] stabilize magnetic skyrmions in chiral systems.…”
Section: Introductionmentioning
confidence: 99%